2009
DOI: 10.1159/000235988
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Decline in the Vascular Event Rate after Transient Ischemic Attack or Stroke in Antiplatelet Trials?

Abstract: Background: We examined the baseline characteristics and the rates of serious vascular events in randomized clinical trials after cerebral ischemia of presumed arterial origin to identify study features that predict vascular event incidence and to identify whether event rates have declined over time. Methods: We performed a systematic review to identify all published randomized controlled trials of patients with stroke or transient ischemic attack of presumed arterial origin that included an aspirin arm. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…Another strength is that we were able to correlate the daily fluid intake with several parameters known to be risk factors for stroke recurrence and known to be influenced by water dilution in the blood. The comparability of our data is reflected by the rate of vascular events in our trial which is similar to the rates of antiplatelet trials in the past decades [18].…”
Section: Discussionsupporting
confidence: 63%
“…Another strength is that we were able to correlate the daily fluid intake with several parameters known to be risk factors for stroke recurrence and known to be influenced by water dilution in the blood. The comparability of our data is reflected by the rate of vascular events in our trial which is similar to the rates of antiplatelet trials in the past decades [18].…”
Section: Discussionsupporting
confidence: 63%
“…12 That analysis examined the rate of major vascular events in the aspirin arms of 34 antiplatelet trials and found no major decline over time. The different findings of our study likely reflect several factors, including 1) broader study selection criteria yielding a larger corpus of trials covering a broader time period with increased statistical power, 2) analysis of a wider set of outcomes, including all stroke alone and fatal stroke alone, in addition to the composite of stroke, MI, and vascular death, and 3) inclusion of older trials using no aspirin in the control arm and of later trials using newer antiplatelet agents more effective than aspirin in the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…9 In Scotland, the adjusted risk of recurrent stroke hospitalization decreased by 27% over 15 years. 10 Another systematic review of more than 23 000 patients treated with aspirin in various studies observed a nonsignificant 0.9% annual relative risk reduction in stroke recurrence over time 11 ; however, that study did not include older studies without an aspirin arm, as did the present report. Lemmens et al 11 reported on only 35% of the patients in trials that averaged a 22% lower mean follow-up than the present study, which could easily explain the absence of statistical significance in their logistic model.…”
Section: Article See P 2111mentioning
confidence: 59%
“…18 In fact, Tables 1 and 2 and Figure 1 of the study by Hong et al 7 suggest a slowing in the declines in all 3 outcome variables for trials that began enrollment in 2000 to 2009 compared with the previous decade, with all 21st century trials reporting recurrent and fatal recurrent stroke risks falling on or above the overall trend lines. The recent decline in recurrent stroke risk, in a period when secondary antithrombotic prophylaxis in trials is virtually universal, may be closer to the smaller 0.9% annual relative risk reduction estimated by Lemmens et al 11 Models such as those by Hong et al 7 are empirical summaries of the past rather than principle-based projections into the future. They provide encouragement that efforts at primary and secondary stroke and vascular prevention strategies may be working, but there is ample reason for concern and no time for complacency.…”
Section: Article See P 2111mentioning
confidence: 65%